2020
DOI: 10.1039/c9fo02051a
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between Chinese propolis and Brazilian green propolis: metabolite profile and bioactivity

Abstract: A comparative study between Chinese propolis and Brazilian green propolis showed that they have a distinct chemome but similar antioxidant and anti-inflammatory potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…These assays are mainly spectrophotometric, which include free radical scavenging (Pobiega et al., 2019), ferric reducing antioxidant power (Ahmed et al., 2017; Gülçin et al., 2010), and electrochemical methods (Rebiai et al, 2011). A lot of results have described the antimicrobial and antibacterial activity of propolis extracts, noting that phenolic compounds, terpenoids and nonaromatic acids are primarily responsible for the inhibiting microorganism growth (Bayram et al., 2017; Martinotti & Ranzato, 2015; Yuan et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These assays are mainly spectrophotometric, which include free radical scavenging (Pobiega et al., 2019), ferric reducing antioxidant power (Ahmed et al., 2017; Gülçin et al., 2010), and electrochemical methods (Rebiai et al, 2011). A lot of results have described the antimicrobial and antibacterial activity of propolis extracts, noting that phenolic compounds, terpenoids and nonaromatic acids are primarily responsible for the inhibiting microorganism growth (Bayram et al., 2017; Martinotti & Ranzato, 2015; Yuan et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition varies depending on the source of the plant. Propolis exhibits a broad spectrum of biological activities, including anticancer, antibacterial (Kasiotis et al., 2017) and antioxidant properties (Yuan et al., 2020). Many studies have indicated a particular interest in the antioxidant activities of propolis using various assays.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the utilization of green propolis extract can provide relief to those who suffer from such disorders. Machado et al (2012), Wang et al (2018), Yuan et al (2020), andSoleimani et al (2021) demonstrated the action of green propolis extract and its isolated compounds such as baccharin ( 19), artepillin C (20) and kaempferide (21) on several fronts of anti-inflammatory action (e.g., reductions in the manifestation of inflammatory genes, production of nitric oxide, and blocking of the manifestation of proinflammatory cytokines). Moreover, the extract increased antiinflammatory factors such as mucosal protective agents like luminal mucin production and expression of anti-inflammatory cytokines (Machado et al, 2012;Soleimani et al, 2021;Wang et al, 2018;Yuan et al, 2020).…”
Section: Anti -Infl Ammatory Ac Tivit Y Of G Reen Prop Olismentioning
confidence: 99%
“…DSS (dextran sodium sulfate) was found to produce typical UC lesions in mice. 24 RAW 264.7 macrophage cells are commonly used to examine the effects of anti-inflammatory compounds. 10,13 Therefore, this study aimed to analyze functional compounds in AE extract by HPLC, and to investigate the protective effects of AE extracts in mice that received DSS, and RAW 264.7 cells exposed to LPS.…”
Section: Introductionmentioning
confidence: 99%